Peneguhan Etika Siaran Dakwah MAJT TV Semarang di Era Konvergensi - Kholid Noviyanto (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, IAI Al-Qodiri Jember, 2023)
The ethics of da’wah broadcasting in today's technological era requires all media sets to transform in digitization of the system. However, in practice, this is used as a strategy to generate selling value so that there are pros and cons related to this, some think that Islamic spread is about the obligation to be conveyed to da’wah partners instead of being marketed through a broadcast capitalization system. There are also those who think that the broadcast system needs to make a profit to develop the broadcast media. Seeing this phenomenon, MAJT TV Semarang has affirmed the ethics of da’wah broadcasts so that television media continues to exist in accordance with the times. This research was revealed using a qualitative type of approach in the form of phenomenology with the intention of revealing the phenomenon in depth by conducting interviews, observations, and documentation to manager of MAJT TV Semarang as well as the existence of other supporting data related to research. The results of this study found that there was a strengthening of da’wah broadcast ethics carried out by MAJT TV Semarang through broadcast media governance ethics, da'i ethics in broadcasting on television, broadcast language ethics, and event segmentation categorization ethics.